Changes Over Time in COVID-19 Severity and Mortality in Patients Undergoing Cancer Treatment in the United States: Initial Report From the ASCO Registry. Issue 4 (25th April 2022) - Mileham, Kathryn F.; Bruinooge, Suanna S.; Aggarwal, Charu; Patrick, Alicia L.; Davis, Christiana; Mesenhowski, Daniel J.; Spira, Alexander; Clayton, Eric J.; Waterhouse, David; Moore, Susan; Jazieh, Abdul-Rahman; Chen, Ronald C.; et al.
Abstract : PURPOSE: People with cancer are at increased risk for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. ASCO's COVID-19 registry promotes systematic data collection across US oncology practices. METHODS: Participating practices enter data on patients with SARS-CoV-2 infection in cancer treatment. In this analysis, we focus on all patients with hematologic or regional or metastatic solid tumor malignancies. Primary outcomes are 30- and 90-day mortality rates and change over time. RESULTS: Thirty-eight practices provided data for 453 patients from April to October 2020. Sixty-two percent had regional or metastatic solid tumors. Median age was 64 years. Forty-three percent were current or previous cigarette users. Patients with B-cell malignancies age 61-70 years had twice mortality risk (hazard ratio = 2.1 [95% CI, 1.3 to 3.3]) and those age > 70 years had 4.5 times mortality risk (95% CI, 1.8 to 11.1) compared with patients age ≤ 60 years. Association between survival and age was not significant in patients with metastatic solid tumors ( P = .12). Tobacco users had 30-day mortality estimate of 21% compared with 11% for never users (log-rank P = .005). Patients diagnosed with SARS-CoV-2 before June 2020 had 30-day mortality rate of 20% (95% CI, 14% to 25%) compared with 13% (8% to 18%) for those diagnosed in or after June 2020 ( P = .08). The 90-day mortality rate for pre-June patients was 28% (21% to 34%) compared with 21% (13% to 28%; P = .20). CONCLUSION: Older patients with B-cell malignancies were at increased risk for death (unlike older patients with metastatic solid tumors), as were all patients with cancer who smoke tobacco. Diagnosis of SARS-CoV-2 later in 2020 was associated with more favorable 30- and 90-day mortality, likely related to more asymptomatic cases and improved clinical management. Abstract : Patients with cancer & SARS-CoV-2 had higher risk of death if B-cell cancer and age >60.